Diseño de una Subestación Eléctrica con un Transformador de Potencia de 500 kVA a 440/257 V para la Empresa Bolivariana de Minerales Ltda - Cediel Álvarez, Cristhian Guillermo; Ruiz Guevara, John Kenny (Universidad Antonio Nariño, 2021)
The present project whose objective is "to design and project a 34.5 kV electrical substation with a 500 kVA power transformer at 440/254 V for the Bolivariana de Minerales LTDA company" where the research methodology used is quantitative since they will be measured, They will calculate, evaluate and quantify variables related to data that can be acquired through electrical substations and their circuits to evaluate the effectiveness of the project. The Bolivarian mineral company does not have an adequate electrical substation for its energy needs, which leads to a difficulty for its economic activity. According to the literature review, it can be concluded that, for the design of an electrical substation, the NTC 2050 and Retie standards must be taken into account; which guarantee that the facilities, equipment and products used in all the generation, transmission, transformation, distribution and final use of electric energy comply with all the legitimate objectives with the protection of life and human health; animal and plant life. The conditions identified in the Bolivarian company according to the review carried out, the total installed capacity is 454.46 kVA, which has a 300 kVA transformer with a voltage level of 13,200 V. With the studies carried out, a 500 kVA transformer was calculated increasing the voltage level to 34.5 kV to reduce the cost of kW / h. which gives us greater reliability.